Morphology and Genetic Diversity of Jabon Putih Seedling from 4 Populations in Sumatra, Nusa Kambangan, Kalimantan, and Sulawesi - Evayusvita Rustam; Dede J. Sudrajat (Foresty Faculty of Hasanuddin University, 2019)
Jabon putih (Neolamarckia cadamba) is a widely distributed potential fast-growing species and is thought to be associated with extensive genetic diversity. The aim of the research was to assess the morphological and genetic variation of jabon putih seedling based on AFLP markers. Randomized block design with 4 replications was used to assess seedling morphological variation on 31 families from 4 populations (Kapuas, Kampar, Nusa Kambangan, Pomalaa) based on traits of seedling height, diameter, sturdiness quotient, number of leaves, leaf length, and leaf width at nursery. AFLP Analysis System I Kit by using dry leaf samples from each family was used. Characteristics of jabon putih seedlings had variation among populations and families within population. Genetic variation within population based on morphological traits had the similar trend with result of AFLP analysis. The highest genetic variation was detected in Kapuas population, followed by Pomalaa, Nusa Kambangan, and Kampar populations. Cluster analysis and UPGMA method had 2 cluster and put down most of families from Kapuas in one cluster separated from other families. Based on the genetic similarity analysis, 26 families could be considered as potential families for the establishment of breeding populations. The study has important practical implications for genetic resources management and for future breeding programs of jabon putih.